Guest

prove that tan 70.tan 65.tan 70.tan 65=1

prove that tan 70.tan 65.tan 70.tan 65=1

Grade:12th Pass

2 Answers

Haroldo Martins
18 Points
10 years ago

tg(70º).tg(65º).tg(70º).tg(65º)>>>>1 - logo isso é impossivel, porem se a equação for

tg(70º).tg(65º).cotg(70º).cotg(65º) , a i sim tg(70º).tg(65º).tg(70º).tg(65º) =1 pois

tg(70º).tg(65º).[1/tg(70º).1/tg(65º)]=1

Haroldo Martins
18 Points
10 years ago

Correção

tg(70º).tg(65º).tg(70º).tg(65º)>>>>1 - logo isso é impossivel, porem se a equação for

tg(70º).tg(65º).cotg(70º).cotg(65º) , ai sim tg(70º).tg(65º).cotg(70º).cotg(65º) =1 e não tg(70º).tg(65º).tg(70º).tg(65º)=1 como escrito anteriormente

pois tg(70º).tg(65º).[1/tg(70º).1/tg(65º)]=1

 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free